KEEFEKTIFAN PENERAPAN KOMBINASI MODEL KOOPERATIF TIPE TGT DAN TIPE NHT - Samsul, Putriyani (Edumaspul: Jurnal Pendidikan, 2017)
This is a pre experimental research which aims were determine the effectiveness of learning mathematics through application of TGT and NHT cooperative models combination which includes: (1) students’ activities, (2) teacher’s activity in managing learning, (3) students’ responses, and (4) mathematics learning student’s achievement after the application of TGT and NHT cooperative models combination. Population is XII IA students at the first semester of academic year 2016/2017. The sample was 28 students taken through random cluster sampling technique. The results showed that: (1) students’ learning activities was good category; (2) the ability of teachers to manage learning was very good category; (3) students responded positively to the learning; and (4) the learning outcomes of after being taught by a combination of TGT and NHT cooperative models achieved 96,43% and the mean score is 83,04 with a standard deviation of 9,75.